GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 14 Oct 2019, 11:09 GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  M26-33

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

Hide Tags

Math Expert V
Joined: 02 Sep 2009
Posts: 58320

Show Tags

16 00:00

Difficulty:   95% (hard)

Question Stats: 46% (02:15) correct 54% (02:30) wrong based on 165 sessions

HideShow timer Statistics

If $$x \gt 0$$, then what is the value of $$y^x$$?

(1) $$\frac{4^{(x+y)^2}}{4^{(x-y)^2}}=128^{xy}$$

(2) $$x \ne 1$$ and $$x^y=1$$

_________________
Math Expert V
Joined: 02 Sep 2009
Posts: 58320

Show Tags

1
3
Official Solution:

(1) $$\frac{4^{(x+y)^2}}{4^{(x-y)^2}}=128^{xy}$$.

Simplify to get: $$4^{(x+y)^2-(x-y)^2}=128^{xy}$$;

Next, apply $$a^2-b^2=(a-b)(a+b)$$ to get: $$4^{4xy}=128^{xy}$$;

$$2^{8xy}=2^{7xy}$$;

Equate the powers: $$8xy=7xy$$;

$$xy=0$$, since given that $$x \gt 0$$ then $$y=0$$, hence $$y^x=0^x=0$$. Sufficient.

(2) $$x \ne 1$$ and $$x^y=1$$. Since $$x \gt 0$$ and $$x \ne 1$$ then the only case $$x^y=1$$ to hold true is when $$y=0$$. So, $$y^x=0^x=0$$. Sufficient.

_________________
Intern  Joined: 01 Feb 2016
Posts: 4

Show Tags

Hi

how is xy=0?; is it because only way 7xy=8xy is when xy=0?
Math Expert V
Joined: 02 Sep 2009
Posts: 58320

Show Tags

2
aqeelnaqvi10 wrote:
Hi

how is xy=0?; is it because only way 7xy=8xy is when xy=0?

8xy = 7xy;

8xy - 7xy = 7xy - 7xy;

xy = 0.

Hope it's clear.
_________________
Intern  Joined: 01 Feb 2016
Posts: 4

Show Tags

I thought one of the two variables must be zero; which will make both sides equal zero and that will prove the equation right
Also, if either x or y is zero that will result zero as the product xy=0 x.0=0

Thanks
Intern  Joined: 17 Jan 2016
Posts: 19

Show Tags

Sorry Bunuel, I'm so confused, how do you apply the difference of squares to get 4xy?
Math Expert V
Joined: 02 Sep 2009
Posts: 58320

Show Tags

1
wmichaelxie wrote:
Sorry Bunuel, I'm so confused, how do you apply the difference of squares to get 4xy?

$$(x+y)^2-(x-y)^2=(x+y+x-y)(x+y-x+y)=2x*2y=4xy$$
_________________
Intern  Joined: 17 Jan 2016
Posts: 19

Show Tags

Wow thank you.
Thread Master - Part Time MBA Programs S
Joined: 11 Jan 2018
Posts: 145

Show Tags

This is a great question.
Intern  B
Joined: 26 Dec 2016
Posts: 34
Concentration: Finance, Entrepreneurship
GMAT 1: 710 Q45 V41 GMAT 2: 610 Q41 V33 GMAT 3: 710 Q47 V40 GPA: 3.5

Show Tags

Bunuel wrote:
wmichaelxie wrote:
Sorry Bunuel, I'm so confused, how do you apply the difference of squares to get 4xy?

$$(x+y)^2-(x-y)^2=(x+y+x-y)(x+y-x+y)=2x*2y=4xy$$

I get (x+y)^2-(x-y)^2=(x+y)(x+y)-(x-y)(x-y)
_________________
GMAT 1: 610
GMAT 2: 710
GMAT 3: 710
Math Expert V
Joined: 02 Sep 2009
Posts: 58320

Show Tags

fvoci wrote:
Bunuel wrote:
wmichaelxie wrote:
Sorry Bunuel, I'm so confused, how do you apply the difference of squares to get 4xy?

$$(x+y)^2-(x-y)^2=(x+y+x-y)(x+y-x+y)=2x*2y=4xy$$

I get (x+y)^2-(x-y)^2=(x+y)(x+y)-(x-y)(x-y)

OK.

1. In my reply I applied $$a^2 - b^2 = (a + b)(a - b)$$.

2. Else you can just expand (x+y)^2 and (x-y)^2: $$(x+y)^2-(x-y)^2=(x^2 + 2xy + y^2)-(x^2-2xy + y^2)=4xy$$
_________________
Intern  B
Joined: 26 Dec 2016
Posts: 34
Concentration: Finance, Entrepreneurship
GMAT 1: 710 Q45 V41 GMAT 2: 610 Q41 V33 GMAT 3: 710 Q47 V40 GPA: 3.5

Show Tags

Bunuel

Perfect! I understand now. Thanks.
_________________
GMAT 1: 610
GMAT 2: 710
GMAT 3: 710
Intern  B
Joined: 12 Jan 2017
Posts: 34
Location: United States (NY)
Schools: Booth '21 (D)
GMAT 1: 710 Q47 V41 GPA: 3.48

Show Tags

Bunuel wrote:
OK.

1. In my reply I applied $$a^2 - b^2 = (a + b)(a - b)$$.

2. Else you can just expand (x+y)^2 and (x-y)^2: $$(x+y)^2-(x-y)^2=(x^2 + 2xy + y^2)-(x^2-2xy + y^2)=4xy$$

For everyone else not understanding how to go from $$a^2 - b^2 = (a + b)(a - b)$$ and $$(x+y)^2-(x-y)^2=(x+y+x-y)(x+y-x+y)=2x*2y=4xy$$, it is simply:
$$(x+y)^2 - (x-y)^2 =(x+y)+(x-y) * (x+y)-(x-y) = 2x*2y = 4xy$$
Intern  B
Joined: 16 Apr 2014
Posts: 15

Show Tags

First, think about statement 2, its quite simple.

Saying x is not equal to 1 and x^y=1, and stem saying x>0
Then just by some intuition, we can deduce that y must 0 and x= positive integer or positive fraction.

Put this values in statement 1. It works.

Both statements are sufficient!
Intern  B
Joined: 25 Nov 2017
Posts: 2

Show Tags

this question hurts my brian T_T

how did the original formula get simplified into

4^(((x+y)^2)-((x-y)^2))
Math Expert V
Joined: 02 Sep 2009
Posts: 58320

Show Tags

1
Mrjack wrote:
this question hurts my brian T_T

how did the original formula get simplified into

4^(((x+y)^2)-((x-y)^2))

Operations involving the same bases:
Keep the base, add or subtract the exponent (add for multiplication, subtract for division)
$$a^n*a^m=a^{n+m}$$

$$\frac{a^n}{a^m}=a^{n-m}$$
_________________
GMAT Club Legend  D
Joined: 18 Aug 2017
Posts: 4987
Location: India
Concentration: Sustainability, Marketing
GPA: 4
WE: Marketing (Energy and Utilities)

Show Tags

Bunuel wrote:
If $$x \gt 0$$, then what is the value of $$y^x$$?

(1) $$\frac{4^{(x+y)^2}}{4^{(x-y)^2}}=128^{xy}$$

(2) $$x \ne 1$$ and $$x^y=1$$

#1
$$\frac{4^{(x+y)^2}}{4^{(x-y)^2}}=128^{xy}$$
solve we get

2*(x+y)^2-2*(x-y)^2=7xy

8xy=7xy
we get
xy=0
so it means x or y is 0 ; so value of $$y^x$$ will be 0 always; sufficient
#2
$$x \ne 1$$ and $$x^y=1$$[/quote]
x is not equal to 1 and x^y =1
so x=0 or say y=0
so value of y^x=0
sufficient
IMO D
_________________
If you liked my solution then please give Kudos. Kudos encourage active discussions.
Intern  B
Joined: 04 Sep 2016
Posts: 16

Show Tags

I think this is a high-quality question and I agree with explanation. 700L questions seem so easy to solve after viewing the solution. Ha! Anytime, I'm solving a very hard question and it's taking me more than a minute, I just move on. I believe I have missed something and when I check the solution, I'm never surprised to see a 1-5line solution. I hope I improve a whole lot before the exam. Kudos, Bunuel.
Senior Manager  G
Joined: 19 Nov 2017
Posts: 253
Location: India
Schools: ISB
GMAT 1: 670 Q49 V32 GPA: 4

Show Tags

Bunuel wrote:
If $$x \gt 0$$, then what is the value of $$y^x$$?

(1) $$\frac{4^{(x+y)^2}}{4^{(x-y)^2}}=128^{xy}$$

(2) $$x \ne 1$$ and $$x^y=1$$

Statement (1) can be re-written as

=> 4^(x^2) * 4^(y^2) * 4^(2xy) / 4^(x^2) * 4^(y^2) * 4^(-2xy) = 128^(xy)

=> 4^(2xy)/4^(-2xy) = 128^(xy)

=> 4^(2xy) * 4^(2xy) = 128^(xy)

=> 16^(xy) * 16^(xy) = 128^(xy)

=> 2^(8xy) = 2^(7xy)

=> 2^(xy) = 1

This is true only when xy = 0

Becuase x>0, y = 0. Hence, value of y^x = 0.

Statement 2 is sufficient as well.

Hence, D
_________________

Vaibhav

Sky is the limit. 800 is the limit.

~GMAC Re: M26-33   [#permalink] 30 Aug 2019, 06:47
Display posts from previous: Sort by

M26-33

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

Moderators: chetan2u, Bunuel

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne  